2004
DOI: 10.1098/rspb.2004.2831
|View full text |Cite
|
Sign up to set email alerts
|

Face pictures reduce behavioural, autonomic, endocrine and neural indices of stress and fear in sheep

Abstract: Faces are highly emotive stimuli and we find smiling or familiar faces both attractive and comforting, even as young babies. Do other species with sophisticated face recognition skills, such as sheep, also respond to the emotional significance of familiar faces? We report that when sheep experience social isolation, the sight of familiar sheep face pictures compared with those of goats or inverted triangles significantly reduces behavioural (activity and protest vocalizations), autonomic (heart rate) and endoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(100 citation statements)
references
References 29 publications
(34 reference statements)
4
85
0
1
Order By: Relevance
“…However, we have shown that female sheep exhibit specific preferences for the faces of individual males independent of social familiarity with them (Kendrick et al 1995). In addition, simple exposure to face pictures of sheep of the same breed (but unfamiliar individuals) reduces behavioural, autonomic and endocrine indices of stress caused by social isolation (da Costa et al 2004).…”
Section: Face Attractionmentioning
confidence: 92%
“…However, we have shown that female sheep exhibit specific preferences for the faces of individual males independent of social familiarity with them (Kendrick et al 1995). In addition, simple exposure to face pictures of sheep of the same breed (but unfamiliar individuals) reduces behavioural, autonomic and endocrine indices of stress caused by social isolation (da Costa et al 2004).…”
Section: Face Attractionmentioning
confidence: 92%
“…Earlier reports have provided some evidence for behavioural lateralization in stress responses [24,28], and that is mainly processed by the right brain hemisphere in mammals [24]. For instance, in sheep social isolation stress is reduced by familiar faces and leads to increased activity in the right hemisphere [51], and strongly lateralized mothers had higher stress response than weakly lateralized mothers following separation from their young [52]. Further, stress induced temperature elevation in the right ear, corresponding to the right hemisphere, has been reported in marmosets [53] and cats [54].…”
Section: Lateralization and Behaviourmentioning
confidence: 98%
“…In large animals, such as sheep or pigs, similar neurobiological factors have been found to be involved in emotional responses, especially in stressful situations. Invasive neurobiological approaches based on functional neuroanatomy (sheep: da Costa et al 2004, Rivalland et al 2007, Vellucci & Parrott 1994, intracerebroventricular pharmacology (pigs: Johnson et al 1994, Salak-Johnson et al 2004, and neurochemical brain content (e.g. in pigs, Kanitz et al 2003, Loijens et al 2002, Piekarzewska et al 1999, Piekarzewska et al 2000, Zanella et al 1996 have demonstrated the involvement of neuropeptides such as CRF and enkephalins in different brain areas including the hypothalamus, brainstem and cortices.…”
Section: Emotional Reactionmentioning
confidence: 99%